A framework for implementing Patient and Public Involvement in mental health research: The PATHWAY research programme benchmarked against NIHR standards. (10th January 2023) - Capobianco, Lora; Faija, Cintia; Cooper, Bethany; Brown, Lindsey; McPhillips, Rebecca; Shields, Gemma; Wells, Adrian
Abstract: Background: Patient and Public Involvement (PPI) in research has become a key component recommended by research commissioners, grant award bodies and specified in government policies. Despite the increased call for PPI, few studies have demonstrated how to implement PPI within large‐scale research studies. Objective: The aim of the current study was to provide a case example of the implementation of a patient advisory group in a large‐scale mental health research programme (PATHWAY) and to benchmark this against UK standards. Method: A PPI group was incorporated throughout the PATHWAY research programme, from grant development to dissemination. The group attended regular meetings and supported participant recruitment, evaluated patient‐facing documents, supported the piloting of the research intervention and co‐developed the dissemination and impact strategy. The implementation of PPI throughout the project was benchmarked against the UK standards for PPI. Results: The inclusion of PPI in the PATHWAY project provided tangible changes to the research project (i.e., improving study documents, co‐developing dissemination materials) but also proved to be a beneficial experience to PPI members through the development of new skills and the opportunity to provide a patient voice in research. We show how PPI was involved across seven study phases and provide examples of implementation of the six UK standards. The study did not include PPI in data analysis but met all the UK standards for PPI. Challenges regarding practical components (i.e., meeting frequency, language use), increasing diversity and PPI members' knowledge of research were highlighted as areas for further improvement. Conclusions: We provide a case example of how PPI can be implemented throughout a research lifecycle and we note the barriers faced and make suggestions for PPI in future implementation and research. Patient and Public Contribution: PPI members were involved throughout the lifecycle of the research programme. The PPI lead was a co‐author on the manuscript and contributed to report writing.